Enterocutaneous and enteroatmospheric fistulas - therapeutics and nursing: literature review (Research, Society and Development, 2023)
The present study aimed to analyze, through a literature review, the therapeutic conduction of nursing and other health professionals to enterocutaneous and enteroatmospheric fistulas, especially post-anastotic fistulas. For this, a literature review was conducted, with searches conducted from August to November 2022, in the electronic databases VHL, PubMed and Scielo, in the following languages: Portuguese, English and Spanish. This research was based on the descriptors found in the DeCS and MeSH, and considering inclusion and exclusion criteria determined by the authors. A total of 2015 articles were found: 727 from the VHL, 1288 from PubMed and without results found in Scielo. Of these, 1275 were excluded because they were duplicated and the other 740 had a title and abstract read. At the end of the analysis, 21 articles were selected because they attended the research. It was possible to conclude that the care of people with enterocutaneous and enteroatmospheric fistulas in the clinical scope has a multidisciplinary approach. It is certain, therefore, that nursing plays an important role in this management and despite the scarcity of studies specifically addressing the subject, it was possible to identify the main nursing care that should be considered in this management.